A New Diagnostic Test for Endometrial Cancer?: Cytology Analysis of Sonohysterography Distention Media. Issue 7 (1st September 2013) - Guralp, Onur; Sheridan, Susan M.; Harter, Josephine; Hinshaw, James Louis; Seo, Songwon; Hartenbach, Ellen M.; Lindheim, Steven; Stewart, Sarah; Kushner, David M.
Abstract : Objective: During saline-infused sonohysterography (SIS), the distension fluid is typically discarded. If cytology analysis could identify those patients with endometrial cancer, many women would be spared from further procedures. Methods: Thirty consecutive patients with clinical stage I or II endometrial adenocarcinoma were prospectively recruited preoperatively. Saline-infused sonohysterography was performed by instilling 5 mL of saline, withdrawing and sending for analysis. Saline was reinfused until complete SIS images were obtained and sent separately for cytology. Results: Of the 30 women enrolled, SIS was technically successful in 29. Demographics included mean age (60.5 ± 6.99 years), body mass index (35.55 ± 8.18 kg/m 2 ), endometrioid histology (76%), and grade (grade 1, 67%). Prestudy diagnostic method included biopsy (70%), dilatation and curettage (17%), and hysteroscopy (10%). Adequate cytology specimens were obtained in 66% of the 5 mL flushes and 72% of the complete SIS collections. Of adequate specimens, the sensitivities to detect endometrial cancer for the 5-mL, complete, and combined fluid samples were 26% (95% confidence interval, 9%–51%), 36% (17%–59%), and 42% (22%–63%). Sensitivity based on the whole study sample (N = 30) was 33% (17%–53%). Statistical significance was not found in the association between a positive test and age, body mass index, grade, diagnostic method, or volume instilled or aspirated. Conclusions: Most patients with early endometrial cancer can undergo SIS procedures with adequate cytology specimens obtained from distention media. However, the sensitivity is low, and refinements are necessary before utilizing as a diagnostic test. In cases with positive results, the patient may be able to avoid other costly and painful procedures.